(3EUdGM GdCOhjI GdeSgdIs - (3MHjT Hf GdMSf GdOeTbj, GdCYSe GdOeTbj , cGf MjkG bHd (B264 (3gs
(3ChdgG (B:s
(3gPG cJGH MHjT Hf GdMSf aj EUdGM GdCOhjI GdeSgdI hfaj eVGQgG hVQhH ESJYeGdgG s
(3BNQgG (B:s
(3hCeG PcQ SGFQ GdCOhjI aCfJ JYQaJ bhGgG hefGaYgG ef cJH GdbOeGA Ef CMHHJ Pdc s
(3fSNI ecQQI ef GdfSNI GdSGHbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B189s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B25 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGj edj (B(1568) s
Keywords: (3GdWHs